1990
DOI: 10.1002/1097-4679(199007)46:4<539::aid-jclp2270460424>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to apply understood ethical principles

Abstract: Recent research suggests a discrepancy between understanding vs. implementation of ethical principles. The present study investigated the relationship between decisions with regard to what “should” vs. what “would” be done in a variety of ethical conflict situations. Additionally, this research examined the influence of the degree of closeness of the respondent to the identified person‐of‐reference in each conflict scenario. The results strongly supported the conclusion that while professional clinicians are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…The Code strikes a balance in respecting confidentiality while providing an exception to allow disclosures of patient confidences under reasonable and narrow circumstances to protect identifiable third persons. Concrete legal and ethical standards are better understood and executed by clinicians [23]. A legislative remedy in Washington could better align clinicians' legal and ethical responsibilities and create a clearer standard for clinician duties.…”
Section: Resultsmentioning
confidence: 99%
“…The Code strikes a balance in respecting confidentiality while providing an exception to allow disclosures of patient confidences under reasonable and narrow circumstances to protect identifiable third persons. Concrete legal and ethical standards are better understood and executed by clinicians [23]. A legislative remedy in Washington could better align clinicians' legal and ethical responsibilities and create a clearer standard for clinician duties.…”
Section: Resultsmentioning
confidence: 99%
“…This result is compatible with more general studies showing a significant difference between “should” and “would do”. Research indicates that PTs “ would” do less than they knew they “ should” when confronted with unprofessional or unethical conduct on the part of colleagues [43]. A possible approach to solving this conflict mentioned in the literature was suggested in our interviews as well: initiating a personal contact with a colleague (or talking about the error in a trustworthy supervision environment) before taking any further steps.…”
Section: Discussionmentioning
confidence: 99%
“…Besides collecting statistics from registration boards and other professional bodies on psychologists' transgressions, or collating self‐report data (e.g., Pope, Keith‐Spiegel, & Tabachnick, ), studies regarding psychology ethics have commonly involved psychologists being presented with vignettes outlining factual or hypothetical ethical dilemmas to which they indicate how they hypothetically would respond and give reasons for their choices (Betan & Stanton, ; Haas, Malouf, & Mayerson, ; Smith et al., ). A measure of ethicalness commonly used was developed by Wilkins, McGuire, Abbott, and Blau (), who defined two categories of psychologists— ethically willing psychologists, who agreed on what they said they would and should do in an ethical dilemma based on ethical standards; and ethically unwilling psychologists, who differed in what they would do and should do. Studies have indicated that many psychologists are ethically unwilling in regard to both real‐life practice ethical dilemmas and in response to hypothetical dilemmas (Bernard, Murphy, & Little, ; Betan & Stanton, ; Kampf, McSherry, Thoams, & Abrahams, ; Schank & Skovholt, ; Smith et al., ).…”
Section: Introductionmentioning
confidence: 99%